2015
DOI: 10.1193/072814eqs120
|View full text |Cite
|
Sign up to set email alerts
|

New Database for Foundation and Ground Performance in Liquefaction Experiments

Abstract: Physical modeling of buildings founded on layers of liquefiable sand has produced insightful data describing ground and building performance. A new publicly available NEEShub database, “FLIQ,” summarizes data from 9 large-scale centrifuge tests with 4 different lead experimentalists, various soil profiles, 49 stations of site and structure response, and more than 60 shaking events, that is, 405 events in total. Example correlations between ground-motion intensity measures and performance measures are presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…AI has traditionally been used to assess the impact of ground shaking on slope stability (e.g., Jibson 2011, among others), and there are several recent studies that continue to support this tradition using statistical correlations between AI and EDPs related to earthquake-induced slope failure (e.g., Barani et al 2010, Hsieh and Lee 2011, Garini and Gazetas 2013, Hadiani et al 2013, Chousianitis et al 2014, 2016, Du and Wang 2014, Chen et al 2015, Fotopoulou and Pitilakis 2015, Khoudi et al 2015, Gülerce and Balal 2017, Du et al 2018). Since Kramer and Mitchell (2006) first concluded that CAV was optimally correlated with excess pore pressure generation in potentially liquefiable soils, recent studies have confirmed and supported this conclusion using statistical correlations between CAV and liquefaction-related and settlement-based EDPs (Dashti et al 2010, Beaty and Perlea 2012, Sideras and Kramer 2012, Khosravifar et al 2014, Allmond et al 2015, Kwan 2015, Bán et al 2016, Daziano and Pérez 2017, Bray and Macedo 2017, Karimi and Dashti 2017, Wang et al 2018), although following Kayen and Mitchell 1997 and Travasarou et al (2003), a few studies have shown that AI rather than CAV correlates better with some liquefaction-based EDPs (Beaty and Perlea 2012, Kwan 2015, Dashti and Karimi 2017).…”
Section: Introductionmentioning
confidence: 94%
“…AI has traditionally been used to assess the impact of ground shaking on slope stability (e.g., Jibson 2011, among others), and there are several recent studies that continue to support this tradition using statistical correlations between AI and EDPs related to earthquake-induced slope failure (e.g., Barani et al 2010, Hsieh and Lee 2011, Garini and Gazetas 2013, Hadiani et al 2013, Chousianitis et al 2014, 2016, Du and Wang 2014, Chen et al 2015, Fotopoulou and Pitilakis 2015, Khoudi et al 2015, Gülerce and Balal 2017, Du et al 2018). Since Kramer and Mitchell (2006) first concluded that CAV was optimally correlated with excess pore pressure generation in potentially liquefiable soils, recent studies have confirmed and supported this conclusion using statistical correlations between CAV and liquefaction-related and settlement-based EDPs (Dashti et al 2010, Beaty and Perlea 2012, Sideras and Kramer 2012, Khosravifar et al 2014, Allmond et al 2015, Kwan 2015, Bán et al 2016, Daziano and Pérez 2017, Bray and Macedo 2017, Karimi and Dashti 2017, Wang et al 2018), although following Kayen and Mitchell 1997 and Travasarou et al (2003), a few studies have shown that AI rather than CAV correlates better with some liquefaction-based EDPs (Beaty and Perlea 2012, Kwan 2015, Dashti and Karimi 2017).…”
Section: Introductionmentioning
confidence: 94%
“…Additional information on layer heights, material types, relative densities or undrained shear strengths, water contents and saturation ratios, as well as selected soil index properties is provided in Table A1 in the online Appendix. Extensive index properties are also available in the data reports of each test, whereas for the soils used at the CGM tests, additional information can be found in Allmond et al (2015a) and Carey et al (2017).…”
Section: Current Test Series In the Databasementioning
confidence: 99%
“…This database follows the paradigm of other databases that assemble test data from similar types of experiments, led by different research teams and conducted at different facilities (e.g. Allmond et al, 2015b). These projects are envisioned to grow over time toward building facility-diverse and research team–diverse, comprehensive, and up-to-date databases that would improve the earthquake engineering community’s understanding of the considered problem by analyzing experiments as a whole.…”
Section: Dynamic Rocking Shallow Foundation Performance Databasementioning
confidence: 99%
“…Foundation rocking is an example of an inelastic SSI system with self-centering and energy dissipating capability. Several researchers (Allmond et al, 2015; Anastasopoulos et al, 2010; Antonellis et al, 2015; Bartlett, 1976; Deng et al, 2012; Drosos et al, 2012; Figini et al, 2012; Gajan and Kutter, 2008; Hakhamaneshi et al, 2012, 2016; Hakhamaneshi and Kutter, 2016; Kutter et al, 2016; Liu et al, 2013; Loli et al, 2014; Pecker et al, 2014; Shirato et al, 2008; Tsatsis and Anastasopoulos, 2015; Wiessing, 1979) have investigated the performance of rocking foundation systems. These studies have demonstrated that rocking foundations have beneficial re-centering and energy dissipation characteristics and that foundation rocking can act as an inelastic isolation mechanism that may be designed to enhance the seismic performance of a soil-foundation-structure system.…”
Section: Background On Rocking Foundationsmentioning
confidence: 99%